Air operations in Israel's war against Hezbollah : learning from Lebanon and getting it right in Gaza - Lambeth, Benjamin S.; Project Air Force (U.S.). Strategy and Doctrine Program; Rand Corporation; United States. Air Force (Santa Monica, CA : RAND, 2011)
In response to a surprise incursion by Hezbollah combatants into northern Israel and their abduction of two Israeli soldiers, Israel launched a campaign that included the most complex air offensive to have taken place in the history of the Israeli Air Force (IAF). Many believe that the inconclusive results of this war represent a (3z(Bfailure of air power." The author demonstrates that this conclusion is an oversimplification of a more complex reality. He assesses the main details associated with the Israeli Defense Forces$1 (B(IDF$1 (Bs) campaign against Hezbollah to correct the record regarding what Israeli air power did and did not accomplish (and promise to accomplish) in the course of contributing to that campaign. He considers IAF operations in the larger context of the numerous premises, constraints, and ultimate errors in both military and civilian leadership strategy choice that drove the Israeli government$1 (Bs decisionmaking throughout the counteroffensive. He also examines the IDF$1 (Bs more successful operation against the terrorist organization Hamas in the Gaza Strip in December 2008 and January 2009, to provide points of comparison and contrast in the IDF$1 (Bs conduct of the latter campaign based on lessons learned and assimilated from its earlier combat experience in Lebanon.s
Introduction -- Highlights of the Campaign -- Key Israeli Air Accomplishments -- Problems in Air Employment -- The Winograd Commission's Findings -- A Second Chance in Gaza -- The Second Lebanon War Reconsidered -- Conclusions.
"RAND Project Air Force."
"The study, 'Israeli Air Operations Against Hezbollah,' was conducted within the Strategy and Doctrine Program of Project Air Force"--Pg. IV.
Includes bibliographical references (p. 345-366) and index.
Also available on the internet via WWW in PDF format.
Keywords: Israel. -- Hel ha-avir.; Hizballah (Lebanon); Arab-Israeli conflict -- 1993- -- Aerial operations, Israeli; Lebanon War, 2006 -- Aerial operations, Israeli